A Prospective Study of Pravastatin in the Elderly at Risk (PROSPER): Screening Experience and Baseline Characteristics - Ford, Ian (BioMed Central, 2002)
BACKGROUND: PROSPER was designed to investigate the benefits of treatment with pravastatin in elderly patients for whom a typical doctor might consider the prescription of statin therapy to be a realistic option. METHODS: The PROspective Study of Pravastatin in the Elderly at Risk (PROSPER) is a randomised, double blind, placebo-controlled trial to test the hypothesis that treatment with pravastatin (40 mg/day) will reduce the risk of coronary heart disease death, non-fatal myocardial infarction, and fatal or non-fatal stroke in elderly men and women with pre-existing vascular disease or with significant risk of developing this condition. RESULTS: In Scotland, Ireland, and the Netherlands, 23,770 individuals were screened, and 5,804 subjects (2,804 men and 3,000 women), aged 70 to 82 years (average 75 years) and with baseline cholesterol 4.0–9.0 mmol/l, were randomised. Randomised subjects had similar distributions with respect to age, blood pressure, and body mass index when compared to the entire group of screenees, but had a higher prevalence of smoking, diabetes, hypertension, and a history of vascular disease. The average total cholesterol level at baseline was 5.4 mmol/l (men) and 6.0 mmol/l (women). CONCLUSIONS: Compared with previous prevention trials of cholesterol-lowering drugs, the PROSPER cohort is significantly older and for the first time includes a majority of women. The study, having achieved its initial goal of recruiting more than 5,500 elderly high-risk men and women, aims to complete all final subject follow-up visits in the first half of 2002 with the main results being available in the fourth quarter of 2002.